Environment and International PoliticsA Study of the Possibilities of Cooperation and ConflictIn Light of New International Variables - Zahraa Mohsen Hajoul (The college of law and political science journal, 2025)
In political science in particular and for those interested in environmental issues in general, the title of the book is "Environment and International Politics - A Study of the Possibilities of Cooperation and Conflict in Light of New International Variables" by researcher Zahraa Mohsen Hajoul. The importance of this topic for many followers is embodied in several aspects, including:1- The novelty of the topic and its professionalism in finding organic connections between the environment and its issues and international politics and its implications at all levels.2- The continuous focus by official and unofficial bodies on the necessities of research related to the environment, especially by the Iraqi Ministry of Higher Education and Scientific Research, which obligated all specializations to address this topic within the framework of specialization.3- Research on this topic represents a serious attempt to bridge the research gap between Iraqi researchers and their counterparts from outside Iraq in terms of interest in environmental issues and their various topics.